2008
DOI: 10.1128/jb.01073-08
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Substitutions in Transmembrane Domains 9 and 10 of GerVB That Affect the Germination Properties of Bacillus megaterium Spores

Abstract: The molecular basis for differences in germinant recognition of Bacillus megaterium QM B1551 spores containing the GerVB and/or GerUB receptor proteins has been examined by site-directed mutagenesis and the construction of cross-homologue chimeras. Focusing on nonconserved residues predicted to reside in transmembrane domains 9 and 10, we demonstrate that GerVB residues Ser319 and Leu345 are of particular importance in defining the specificity and apparent affinity of the receptor for germinants. Kinetic analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 34 publications
(40 reference statements)
1
23
0
Order By: Relevance
“…We do not have a firm explanation for this result, although KBr germination of B. megaterium spores is mediated by one or more GRs, albeit perhaps fortuitously (6,7). However, given the chaotropic effects of KBr and the potential for nonspecific inhibition of germination at high KBr concentrations, perhaps very high KBr concentrations can both stimulate spore germination via GRs and nonspecifically inhibit germination, and the nonspecific effects decrease much more than the effects on GRs as KBr concentrations decrease.…”
Section: Discussionmentioning
confidence: 70%
“…We do not have a firm explanation for this result, although KBr germination of B. megaterium spores is mediated by one or more GRs, albeit perhaps fortuitously (6,7). However, given the chaotropic effects of KBr and the potential for nonspecific inhibition of germination at high KBr concentrations, perhaps very high KBr concentrations can both stimulate spore germination via GRs and nonspecifically inhibit germination, and the nonspecific effects decrease much more than the effects on GRs as KBr concentrations decrease.…”
Section: Discussionmentioning
confidence: 70%
“…Plasmid pGEM⌬gerKA::Km was subsequently isolated from transformant E. coli and then used as a template to PCR amplify the ⌬gerKA::Km cassette, introducing MfeI sites at the 5= ends, before digestion and ligation with EcoRI-restricted pUCTV2 (21) to yield pUCTV-⌬gerKA::Km. This plasmid was introduced into B. megaterium PV361 via polyethylene glycol (PEG)-mediated protoplast transformation (19). A Tc s Km r transformant, which had undergone double homologous recombination to introduce an insertion and deletion at the gerKA locus, was isolated after incubation of several single-crossover colonies at 42°C in the absence of antibiotics.…”
Section: Construction Of B Megaterium Gr Mutant Strainsmentioning
confidence: 99%
“…In evolutionary terms, Bacillus megaterium is a key member of the Bacillus genus, forming a deep-rooted phylogenetic branch that is genetically and phenotypically distinct from the Bacillus subtilis and Bacillus cereus groups (11). Strains and species from all three groups have for several decades been employed in numerous studies on spore germination; however, whereas the different classes of GRs have been examined in vitro by mutational analyses in B. subtilis (2,12), B. cereus (13,14), and Bacillus anthracis (6,15), detailed analyses of B. megaterium's GRs, GerU apart (16)(17)(18)(19), have not been conducted. Hence, the objective of the present work was to characterize the expression, function, and germinant recognition profiles associated with novel B. megaterium spore germinant receptors.…”
mentioning
confidence: 99%
“…However, while a single residue in TM10 of GerVB (leucine 345) was shown to be crucial to the proline-mediated germinative response, amino acid substitution and kinetic analyses indicated that this position is not directly involved in binding to the germinant (5). Indeed, while a number of residues have been identified as being important to receptor function, particularly in response to proline-and leucine-stimulated germination, the residues involved directly in binding to germinants-and, in particular, those involved in binding to glucose-have yet to be identified.…”
mentioning
confidence: 99%
“…In particular, experiments conducted in our own laboratory using cross-homologue chimeric constructs and site-directed mutagenesis (SDM) experiments with two closely related receptor B proteins have begun to yield insights into the structure-function relationships in the Bacillus megaterium GerU receptor (4,5). GerU structural genes, which are plasmid-borne on the wild-type QM B1551 strain, are required to initiate the B. megaterium QM B1551 germinative response to glucose, proline, leucine, and inorganic salts (6,36).…”
mentioning
confidence: 99%